Medical Officer, Center for Nuclear Medicineand Ultasound,Post Box # 16 Rangpur 5400,Bangladesh - TAHER, M.A.; REAJUL ISLAM, MD. (The ASEAN Journal of Radiology, 2023)
Radionuclide renogram was performed on a hypertensive adult male which revealed renovascular hypertension. We report it as a rare case.